Dialog swojskości i obcości w powieści Most na Drinie Ivo Andricia a modyfikacja znaczeń ewokowanych nazw własnych w przekładzie na język polski - Ecler-Pasku, Martyna (Przekłady Literatur Słowiańskich, 2015)
The dialogue of familiarity and foreignness in Ivo Andric’s novel The Bridge on the Drina and the modification of evocative meanings of the proper names in the Polish translation The article discusses the problem of the cultural meanings of proper names in the translation process of the novel ‘The Bridge on the Drina’ by Ivo Andric and its translation into Polish. The translation is considered to be the symbolic communication of two semiotic spaces (semiosphere) which cultivate the cultural heritage, historical experience and the hierarchy of values of a particular community. Since the culture of Bosnia and Herzegovina is heterogeneous, the opposition between familiarity and foreignness can not be considered only as binary. Some of the proper names in the novel simultaneously evoke the space of familiarity and the space of foreignness. In the case of ethnonym ‘Turks’ we will try to present several translational constraints which stem from the semantic and cultural aspects of proper names. We also examine the problem of polysemy of the proper name ‘Turks’ which functions as an apellative. On the basis of the five translational methods we will show in what way both the cultures (the one of the original work and the one of the translation) limit the translator in choosing equivalents. Key words: Ivo Andric, literary translation, proper names, semiosphere, opposition familiarity/ foreignness